Effect of dietary glncosinolates on nutrient utlization and growth of crossbreed claves - TYAGI, AMRISH; DAS, SRINIBAS; SINGHAL, K K (The Indian Journal of Animal Sciences, 2011)
Crossbred male calves (18) of similar age (8-9 months) and body weight (110-190 kg) were distributed into 3 groups of 6 each on the basis of their body weight. The calves in control group (01) were fed on concentrate mixture containing groundnut oilcake as a sole protein supplement, which was replaced by mustard oilcake (Brassica carnpestris) (G2) and taramira oilcake (Eruca sativa) (G3), respectively. Wheat straw ad lib. and leguminous fodder (1 kg) was fed to all the calves for 90 days. Gluconapin and glucobrassica napin were the major glucosinolates of mustard oilcake., whereas, glucoerucin was the major glucosinolate in taramira oilcake. Total glucosinolates content ofconcentrate mixtures G1, G2 and G3 was 0, 17.59 and 17.50 mmol/g, respectively. Dry matter intake, nutrient digestibility, nitrogen balance, serum T3 and T4 levels and growth rate of growing calves indicated that protein supplied by groundnut oilcake in the concentrate mixture can be replaced with mustard or tararnira oilcakes without affecting the growth performance and nutrient digestibility in crossbred calves. It was concluded that glucosinolates, irrespective of their source, were not harmful at 17.50 mmol/g level in concentrate mixture for the crossbred calves.Â